Nanocasting Process to Pore-Expanded Ordered Mesoporous Carbons with 2D Hexagonal Mesostructure - Chongwen Jiang; Keyuan Zhou; Xin Zhong (International Journal of Chemical Engineering)
Pore-expanded ordered mesoporous carbons with 2D hexagonal mesostructure were synthesized by a simple nanocasting process. We adopted sucrose as carbon precursors, mesoporous silica materials SBA-15 as the hard templates, and hexane as micelle swelling agents. The pore size distribution of OMCs was narrow and centered at 5.4 nm, which is larger than the upper limit of pore diameters typically reported for CMK-3. The BET surface area and mesopore volume of PE-CMK-3 can reach to 1213.47 m2/g and 1.56 cm3/g, respectively, indicating that choosing large pore size materials as template is good for preparation of high performance of OMCs.